The Influence of Papaya Leaf Juice on Breast Milk Sufficiency on Posyandu Working Area Of Tanjung Aru Village - Ariestantia, Dwi Riyan; Handayani, Puji (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Background :Maternal and child health indicator a nation's health status achievement. The formation of quality humans beings starts when the baby is in the wom, accompanied by breast milk. Health Law No.36 of 2009 and Regulation No.33 of 2012 regarding breastfeeding states that every baby must receive exclusive breastfeeding. However, many mothers stop breastfeeding on the grounds of insufficient breast milk. To address the issue of mothers’ breast milk production, pharmacological and non-pharmacological efforts to promote breast milk. Giving papaya leaf juice is one of the non-pharmacological efforts to promote breast milk. Young papaya leaves contain 35mg/100mg of Tocophenols, alkaloids, saponins, potassium and papain enzymes that can stimulate the hormones prolactin and oxytocin, which play a role in the breastfeeding process. Purpose : The study aimed to know the effect of giving papaya leaf juice on indicators of breast milk adequacy at Integrated Health Service Post, Tanjung Aru Village. Method :This research was Pre- Experimental (one group pre-posttest design). The sample amounted to 6 respondents, was taken by the Saturated Sampling technique. For seven days, 100 ml of papaya leaf juice was given in the morning and evening. Analysis of the data used is the Paired t-Test. Results: The average weight of infants before the mother consumed papaya leaf juice was 5400 grams and after consuming papaya leaf juice increased body weight with an average of 5506.67 grams with standard deviation values before 0.927 and after 0.926. The Paired t-Test showed that the p value = 0.013 < 0.05, so there was an effect of giving papaya leaf juice on indicators of breast milk adequacy in Integrated Health Service Post, Tanjung Aru Village. Conclusion: There is an effect of giving papaya leaf juice on indicators of breast milk adequacy.